The effect of vibration of the controlled object on the measuring relay system - Величко, А.Ф.; Нетребенко, К.В. (Radiotekhnika, 2017)
The increase in accuracy and reliability of measuring the technological process parameters is an urgent task. However, the industrial vibration is one of the most significant obstacles to its implementation. The mechanism of vibration impact on the radiowave phase shift — the information parameter of the signal used in the measurement relay system (MRS) is described here. Mathematical modeling has confirmed the notability of the impact of vibration on the measurement accuracy, and also revealed the conditions under which this influence is reduced to zero. These observations form the basis of the proposed processing algorithm for MRS to reduce the impact of vibration on the measurement accuracy.